(3fNHI GdJaGMI aj Yde GdeSGMIs - (3YHO GddWja GdOeTbjs; (3CHh GdMSf CMeO Hf eMeO Hf EHQGgje GdCTYQj GdfSGHg Gdjefjs
(3ChdgG (B:s
(3ef HYO MeO Gddg hGdUdGI Ydi QShd cGed GdUaGJ GdebOeI ai JYQja GdeSGMI hGdEUWdGMGJ s
(3BNQgG (B:s
(3cedJ fNHI GdJaGMI ai Yde GdeSGMI HMeO Gddg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde JSdjekG s
(3GdJaGMI ai GdeSGMI GfXQ cTa GdXfhf L(B1 (3U` (B426s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B426s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(495) s
Keywords: (3GdQjGVjGJs